(untitled) (Carte Romanze, 2024)
The essay proposes the critical edition of four cantigas, one de amor and three de amigo, by Roi Martinz d’Ulveira, a Portuguese troubadour presumably active in the last quarter of the 13th century. The edition is accompanied by an introduction on the author and the manuscript tradition of his work, the translation of the poems and a detailed commentary, divided into metrical analysis, an introductory presentation and explanatory notes to the verses.